Role of Extracellular Vesicles in Autoimmune Pathogenesis - Wu, Wen-Cheng; Song, Sheng-Jiao; Zhang, Yuan; Li, Xing (Frontiers in Immunology, 2020)
Autoimmune diseases are conditions that emerge from abnormal immune responses to natural parts of the body. Extracellular vesicles (EVs) are membranous structures found in almost all types of cells. Because EVs often transport “cargo” between cells, their ability to crosstalk may be an important communication pathway within the body. The pathophysiological role of EVs is increasingly recognized in autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus, Sjogren's syndrome, and Type 1 diabetes. EVs are considered as biomarkers of these diseases and may provide therapeutic targets for drug delivery. This article outlines existing knowledge on the role of EVs in autoimmune diseases and provides advances in their potential as biomarkers and treatment agents.